A Computer-assisted Approach to the Analysis of Translation Shifts - Munday, Jeremy (Meta, 1998)
AbstractThis article is an analysis of shifts in Seventeen Poisoned Englishmen, Edith Grossman's English translation, of a novel in Spanish by Gabriel García Márquez. It makes use of a variety of basic tools of corpus linguistics as aids to the inductive exploration of texts.